Gestational Diabetes and the Offspring: Implications in the Development of the Cardiorenal Metabolic Syndrome in Offspring - Garcia-Vargas, Liliana (S. Karger AG, 2012)
The risk of developing type 2 diabetes and cardiovascular disease in women who had previously been diagnosed with gestational diabetes (GDM) is well established. There is increasing evidence that the offspring of women with GDM are at increased risk for the development of all components of the cardiorenal metabolic syndrome. Overall, it appears that these offspring have an increased risk for overweight/obesity, insulin resistance, higher blood pressure, renal disease, and type 2 diabetes. However, distinct differences in regional populations, lack of routine screening and treatment of GDM worldwide, and long follow-up periods for offspring represent a challenge in assessing the risk for development of these abnormalities in the offspring of women who have had GDM.